2023
DOI: 10.1093/ofid/ofad224
|View full text |Cite
|
Sign up to set email alerts
|

Cefazolin vs Second-line Antibiotics for Surgical Site Infection Prevention After Total Joint Arthroplasty Among Patients With a Beta-lactam Allergy

Abstract: Background Cefazolin is a first-line agent for prevention of surgical site infections (SSIs) after total joint arthroplasty. Patients labeled as allergic to beta-lactam antibiotics frequently receive clindamycin or vancomycin perioperatively due to the perceived risk of a hypersensitivity reaction after exposure to cefazolin. Methods This single-system retrospective review included patients labeled as allergic to penicillin o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Clindamycin also has an increased risk of C. difficile infection in this population [62 ▪ ]. Norvell et al confirmed that using cefazolin over a second line antimicrobial prophylaxis in total hip or knee arthroplasties had fewer SSI (0.9% vs 3.8%; P < .001) and PJI (0.1% vs 1.9%) [59 ▪▪ ]. With the new practice recommendations for drug allergy from the American Academy of Allergy, Asthma, and Immunology (AAAAI) [64 ▪ ] and the documented safety of direct oral amoxicillin challenge on delabelling penicillin allergies [65,66 ▪ ], this should be a major target in using antibiotics wisely to improve antibiotic use and prevent SSI.…”
Section: Surgical Antibiotic Prophylaxismentioning
confidence: 94%
See 1 more Smart Citation
“…Clindamycin also has an increased risk of C. difficile infection in this population [62 ▪ ]. Norvell et al confirmed that using cefazolin over a second line antimicrobial prophylaxis in total hip or knee arthroplasties had fewer SSI (0.9% vs 3.8%; P < .001) and PJI (0.1% vs 1.9%) [59 ▪▪ ]. With the new practice recommendations for drug allergy from the American Academy of Allergy, Asthma, and Immunology (AAAAI) [64 ▪ ] and the documented safety of direct oral amoxicillin challenge on delabelling penicillin allergies [65,66 ▪ ], this should be a major target in using antibiotics wisely to improve antibiotic use and prevent SSI.…”
Section: Surgical Antibiotic Prophylaxismentioning
confidence: 94%
“…Penicillin allergy reporting significantly impacted antibiotic usage in surgical prophylaxis with more use of second line antibiotic prophylaxis [59 ▪▪ ]. It has been well described that penicillin allergies are over-reported, and that cross reactions with cefazolin does not occur due to side chain differences [60].…”
Section: Surgical Antibiotic Prophylaxismentioning
confidence: 99%
“…A thorough allergy history is necessary: it is problematic that in a recent U.K. study, in two-thirds of patients with documented penicillin allergy, there were no details recorded [4]. Patients who report a β-lactam allergy are at higher risk of SSIs and C. difficile infection due to the use of alternative broad-spectrum and often inferior antibiotics [4,33,55,56]. Among these patients, only a small proportion have a true allergy, and the proper tools should be utilized for the delabeling [55,56].…”
Section: The Use Of Antibiotics In Surgical Departments-the Importanc...mentioning
confidence: 99%
“…Patients who report a β-lactam allergy are at higher risk of SSIs and C. difficile infection due to the use of alternative broad-spectrum and often inferior antibiotics [4,33,55,56]. Among these patients, only a small proportion have a true allergy, and the proper tools should be utilized for the delabeling [55,56].…”
Section: The Use Of Antibiotics In Surgical Departments-the Importanc...mentioning
confidence: 99%
“…Multiple studies have identified an increased SSI risk in penicillin-allergic patients with the use of beta-lactam alternatives for perioperative prophylaxis, which is present across multiple procedure types, including orthopedic surgeries, oral and maxillofacial surgeries, obstetric procedures and gynecologic surgeries, colorectal surgeries, and cardiac surgeries [4][5][6][7][8][9]. Blumenthal et al found that penicillin-allergic patients had an adjusted odds ratio of 1.51 (95% CI 1.02-2.22) for developing an SSI following a surgical procedure compared to those without a reported allergy, which they attributed to the use of antibiotics other than cefazolin in these patients [9].…”
Section: Ssi Risk In Penicillin-allergic Patientsmentioning
confidence: 99%